Pengaruh Kompetensi Sosial Guru Terhadap Minat Belajar PAI Siswa Kelas VIII SMP Swasta Taman Siswa Sidomulyo Kab. Batubara - Safitri, Dewi; Hafsah; Syukri, Makmur (PT. Kreasi Karya Majakata, 2025)
This study aims to analyze the effect of teachers' social competence on students' learning interest in Islamic Religious Education (PAI) for 8th-grade students at SMP Swasta Taman Siswa Sidomulyo, Batubara Regency. This research employs a quantitative approach, with the entire population of 60 students serving as the sample (total sampling). Data collection instruments include observations and questionnaires, while the data analysis technique used is the t-test. The results indicate that the t-calculated value for teachers' social competence is 7.516, while the t-table value with 58 degrees of freedom (df) is 1.671. With a significance value of 0.000 (< 0.05), these findings suggest that teachers' social competence has a significant and positive impact on students' learning interest in Islamic Religious Education.